Cellular Mechanisms Contributing to the Functional Heterogeneity of GABAergic Synapses - Campbell, Benjamin F. N.; Tyagarajan, Shiva K. (Frontiers in Molecular Neuroscience, 2019)
GABAergic inhibitory neurotransmission contributes to diverse aspects of brain development and adult plasticity, including the expression of complex cognitive processes. This is afforded for in part by the dynamic adaptations occurring at inhibitory synapses, which show great heterogeneity both in terms of upstream signalling and downstream effector mechanisms. Single-particle tracking and live imaging have revealed that complex receptor-scaffold interactions critically determine adaptations at GABAergic synapses. Super-resolution imaging studies have shown that protein interactions at synaptic sites contribute to nano-scale scaffold re-arrangements through post-translational modifications, facilitating receptor and scaffold recruitment to synaptic sites. Additionally plasticity mechanisms may be affected by the protein composition at individual synapses and the type of pre-synaptic input. This mini-review examines recent discoveries of plasticity mechanisms that are operational within GABAergic synapses, and discusses their contribution towards functional heterogeneity in inhibitory neurotransmission.